Rapporter - Moe, Bjarke; Ørbæk Jensen, Anne; Nissen, Peter E.; Fjeldsøe, Michael (Danish Yearbook of Musicology, 2009)
Research Projects Foreign Music in Copenhagen and Rostock in the First Half of the 17th Century (Bjarke Moe) Conferences Research on Choirs and Choral Singing, Lund, October 2008 (Anne Ørbæk Jensen) ‘The Year of Singing’, University of Southern Denmark, November 2008 (Peter E. Nissen) Carl Nielsen: Texts and Contexts, Manchester 2009 (Michael Fjeldsøe) Danish Musicological Society, 2008 (Anne Ørbæk Jensen)